Impacts of Major Crop Production on the Agricultural Sector in Bangladesh: A Time Series Analysis - Dey, Sudip (International Journal of Sustainable Agricultural Research, 2022)
The main objective of this research article is to analyze the impact of the production of some major crops, namely rice, jute, wheat, sugarcane, and potato on the agriculture sector in Bangladesh. The agriculture sector is considered an important sector of the Bangladeshi economy, which supplies a significant proportion of the gross domestic product (GDP). Annual time-series data for the period 1988–2017 is used for the study. Several econometric techniques are employed to examine the data, including the augmented Dickey-Fuller (ADF) test, Johansen cointegration test, and ordinary least squares (OLS) method. To validate the model, some residual diagnostic tests, namely a normality test, heteroskedasticity test, serial correlation test, and stability diagnostic test are conducted. The findings of the study demonstrate that there are two cointegrating equations in the model. Furthermore, both wheat and jute production have a significant positive impact on the agriculture sector. Although the impacts of rice and potato production on the agriculture sector are positive, these are not significant at the 5 or 10 percent significance level. On the other hand, sugarcane production has a negative and significant impact on the agriculture sector, which was not expected. Based on the results, this paper recommends that the government of Bangladesh should focus on designing and implementing new funding policies and subsidies to improve the growth, production, and development of the sugarcane sector. Finally, the government should be concerned about climate change-related factors that negatively affect crop production in Bangladesh.